Climate change impacts on water resources and reservoir management in the Seine river basin (France). Issue 5 (1st October 2016) - Dorchies, David; Thirel, Guillaume; Perrin, Charles; Bader, Jean-Claude; Thepot, Régis; Rizzoli, Jean-Louis; Jost, Claudine; Demerliac, Stéphane
Abstract : The Seine River Basin has to face major issues on water resources due to a variety of uses and increasing pressure. Satisfying these water needs is a huge challenge on this basin that hosts the most urbanized and densely populated area in France: more than 6.5 millions inhabitants in the Paris region are supplied with drinkable water coming from rivers while one nuclear power plant and two coal-fired plants ensure power generation in the region. Furthermore, several large wastewater treatment plants (incl. the largest one in Europe) release their waters into the Seine, with possible consequences on the quality of water during low flows. The Seine Grands Lacs basin authority owns and manages four large artificial reservoirs on the river Seine and its tributaries (totaling a capacity of 800 hm3) with two main goals: flood alleviation and low-flow augmentation. The CLIMAWARE research project (2010-2014) characterized the impacts of climate change on flows of the Seine River Basin and on reservoir management by mid-21st century. Performance indicators representative of the tension on water resources were calculated to assess the impact of climate change. Various adaptation measures were tested including the modification of the objective seasonal filling curves, as well as modifications of the real-time management techniques. Adaptation measures can bring some improvements, but even with this adaptive management, the indicators show that the impacts of climate change on low flows will be major on the basin.